Dynamic Range Expansion Method of Three-component HTc SQUIDs Magnetometer. Issue 4 (April 2020) - Gong, X W; Guo, J Y; Du, J Q; Teng, D; Wang, Y
Abstract: In view of the small dynamic range of the three-component high-temperature superconducting quantum interference device (HTc SQUID) magnetometer and it is easy to exceed the measurement range when working in the field without magnetic shielding environment. A dynamic range expansion method based on step compensation is proposed. By setting a magnetic compensation coil on each axis of the three-component HTc SQUIDs magnetometer probe, a current is passed to generate a magnetic field opposite to the direction of the external magnetic field to offset most of the magnetic field to be measured. The measured values are calculated and processed to obtain the magnetic field value to be measured. The test results show that the method can greatly improve the dynamic range without reducing the sensitivity of the magnetometer, which can work stably in a non-magnetic shielding environment and meet the requirements of field geophysical magnetic exploration.